Theoretical Study of Chloro-N-(4-methoxybenzylidene)aniline Derivatives as Corrosion Inhibitors for Zinc in Hydrochloric Acid. (26th December 2013) - Kumar, S.; Ladha, D. G.; Jha, P. C.; Shah, N. K.
Abstract : The density functional theory (DFT) was used to investigate the corrosion inhibition of three inhibitors on zinc. Quantum chemical parameters such as the energy of highest occupied molecular orbital (E HOMO ), the energy of lowest unoccupied molecular orbital (E LUMO ), energy gap( Δ E ), hardness( η ), softness( σ ), electrophilicity index( ω ), the fraction of electrons transferred( ΔN ) from inhibitor molecule to the metal surface, energy change when both processes occur, namely, charge transfer to the molecule and backdonation from the molecule (Δ E b a c k d o n a t i o n ), natural charge( q N ), and Fukui functions have been calculated by using B3LYP/6-31+G(d) basis set. The relation between the inhibition efficiency and quantum chemical parameters has been discussed in order to elucidate the inhibition mechanism of the chloro-N-(4-methoxybenzylidene)aniline derivatives.